Results of INSSURE Method in the Treatment of Respiratory Distress Syndrome in Premature Infants at Bac Ninh Obstetric Pediatric Hospital - Thuy, Tran Thi; Xuan, Ngo Thi; Kien, Pham Trung; Canh, Hoang Ngoc (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2017)
OBJECTIVES: To evaluate the results of the INtubate-SURfactant-Extubate (INSURE) method in the treatment of respiratory distress syndrome in premature infants at Bac Ninh obstetric pediatric hospital from March to September 2017. METHODS : A descriptive study was conducted on 50 preterm infants with respiratory distress syndrome. The infants were treated with INSURE method . RESULTS : Of the 50 infants, 29 (58.0%) were male. All of infants,  49 (98.0%) gestational age under 32 weeks, of which 56.0% was less than 30 weeks. The infants birth weight less than 1500 grams accounted for 78.0%, of which 28.0% under 1000 grams. Only 40.0% of mothers were injected with corticosteroid before giving birth. The most common symptoms are cyanosis , apnea neoatorum  > 10 seconds; lower temperature. X.ray III is 92.0%. All infants were pumped pulsed surfactant before 6 hours, intubated endotracheal tube and was removed within 50 minutes. There were 13 children (26.0%) had to have mechanical ventilation, the highest rate of reintroduction in infants birth weight less than 1000 grams. The rate of SpO2 increased, the FiO2 and Siverman index decreased and remained stable significantly after 6 hours of treatment. The complication rate was 4.0%. Treatment outcomes were only associated with birth weight (p<0.05). CONCLUSIONS: INtubate-SURfactant-Extubate is effective methods in treatment of infants with respiratory distress syndrome (RDS).